2010
DOI: 10.1111/j.1525-1446.2009.00823.x
|View full text |Cite
|
Sign up to set email alerts
|

Parental Hesitation in Immunizing Children in Utah

Abstract: The manner in which immunization information is shared with hesitant parents can be particularly important. There is a need for health care providers to assess and increase parental knowledge regarding immunizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 16 publications
1
41
0
Order By: Relevance
“…17 Vaccine refusals and delays are a threat to herd immunity, 23 and there is evidence to suggest that parents are unaware of how immunization results in protection. 16 Research concerning pediatric vaccine acceptance has evaluated vaccine hesitancy among parents [24][25][26][27] and strategies for increasing vaccine acceptance. One pilot study evaluated the impact of tailored messages to address specific concerns contributing to vaccine hesitancy.…”
Section: Discussionmentioning
confidence: 99%
“…17 Vaccine refusals and delays are a threat to herd immunity, 23 and there is evidence to suggest that parents are unaware of how immunization results in protection. 16 Research concerning pediatric vaccine acceptance has evaluated vaccine hesitancy among parents [24][25][26][27] and strategies for increasing vaccine acceptance. One pilot study evaluated the impact of tailored messages to address specific concerns contributing to vaccine hesitancy.…”
Section: Discussionmentioning
confidence: 99%
“…20 For VHPs, barriers to vaccination have been well described, 13,18,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] and most barriers are centered on concerns about vaccine safety. Surveys or interviews conducted with VHPs have found that VHPs are more likely to state that vaccines are not safe.…”
Section: Barriers To Vaccinationmentioning
confidence: 99%
“…The success of routine immunization programs has resulted in decreased incidences of many VPDs in the United States, prompting some parents to turn their concern from the consequences of diseases to the risks of vaccines themselves (Luthy et al, 2010). A recent study found that 8% of parents believed it was better for the child to get the disease naturally rather than receive an immunization for protection (Rogers, 2014).…”
Section: Lack Of Perceived Needmentioning
confidence: 98%
“…Common themes of parental vaccine hesitancy emerged from the literature: (a) lack of perceived need for vaccines, (b) safety of vaccines, (c) lack of trust in health care providers and government, (d) perceived lack of involvement in the decision-making process, (e) vaccines and autism, (f) immune system overload, (g) lack of adequate time and resources, and (h) religious objections to vaccines (Luthy, Beckstrand, & Callister, 2010;Rogers, 2014;Smith & Marshall, 2010).…”
Section: Common Themesmentioning
confidence: 99%